2023
DOI: 10.3390/ijerph20043491
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes after Stroke in Patients with Atrial Fibrillation: A Single Center Study

Abstract: Atrial fibrillation (AF) is known to be a significant risk factor for poor prognosis after stroke. In this study, we compared differences in long-term outcomes after ischemic stroke among patients with AF and sinus rhythm (SR). We identified patients admitted to the reference Neurology Center between 1 January 2013 and 30 April 2015, inclusive, with acute ischemic stroke. Of the 1959 surviving patients, 892 were enrolled and followed for five years or until death. We analyzed the risk of stroke recurrence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The worse prognosis in the AF group was observed to be related to older age and multi-comorbidities in those groups. 17 CKD also notably showed higher in patients with in-hospital mortality in this study. Patients face a 30fold increased risk of stroke morbidity and a case mortality rate of nearly 90%.…”
Section: Discussionsupporting
confidence: 59%
“…The worse prognosis in the AF group was observed to be related to older age and multi-comorbidities in those groups. 17 CKD also notably showed higher in patients with in-hospital mortality in this study. Patients face a 30fold increased risk of stroke morbidity and a case mortality rate of nearly 90%.…”
Section: Discussionsupporting
confidence: 59%
“…Our findings were consistent with previous studies, highlighted age and NIHSS score as primary independent risk factors for short-and long-term mortality in patients with ischemic stroke (IS) and AF. [29][30][31][32][33] Age is closely intertwined with stroke incidence and severity. 34 Previous researches reported that the mortality of patients with stroke rose with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, multivariate analysis revealed that this association was mostly due to the increased age and greater initial stroke severity in AF patients. A recent study investigating long-term prognosis in AIS patients with and without AF demonstrated a significantly higher rate of one-year mortality post-stroke in AF patients [102]. Similarly, this association was no longer significant after adjusting for comorbidities such as heart failure and the greater age and baseline stroke severity in AF patients.…”
Section: Impact Of Atrial Fibrillation On Stroke Outcomesmentioning
confidence: 94%